2018
DOI: 10.1096/fj.201800713rr
|View full text |Cite
|
Sign up to set email alerts
|

Segregation of dopamine and glutamate release sites in dopamine neuron axons: regulation by striatal target cells

Abstract: Dopamine (DA) is a key regulator of circuits controlling movement and motivation. A subset of midbrain DA neurons has been shown to express the vesicular glutamate transporter (VGLUT)2, underlying their capacity for glutamate release. Glutamate release is found mainly by DA neurons of the ventral tegmental area (VTA) and can be detected at terminals contacting ventral, but not dorsal, striatal neurons, suggesting the possibility that target-derived signals regulate the neurotransmitter phenotype of DA neurons.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(55 citation statements)
references
References 53 publications
4
51
0
Order By: Relevance
“…To recapitulate, we find here that expression of Th and Vglut2 is reciprocally regulated in DA neurons in response to cellular stress. While previous work showed that the presence of striatal cells reinforces the Th phenotype of DA neurons (Fortin et al, 2019), a low dose of MPP+ results in the opposite and favors their glutamatergic phenotype, as revealed by an increase in Vglut2 mRNA copy number. Finally, our in vitro data suggest the possibility that upregulated GDNF expression in the post-lesional brain could elevate Vglut2 expression above detection level and as such could be involved in the observed enhanced prevalence of Vglut2 expression in DA neurons in the post-lesional brain in vivo .…”
Section: Resultsmentioning
confidence: 78%
See 4 more Smart Citations
“…To recapitulate, we find here that expression of Th and Vglut2 is reciprocally regulated in DA neurons in response to cellular stress. While previous work showed that the presence of striatal cells reinforces the Th phenotype of DA neurons (Fortin et al, 2019), a low dose of MPP+ results in the opposite and favors their glutamatergic phenotype, as revealed by an increase in Vglut2 mRNA copy number. Finally, our in vitro data suggest the possibility that upregulated GDNF expression in the post-lesional brain could elevate Vglut2 expression above detection level and as such could be involved in the observed enhanced prevalence of Vglut2 expression in DA neurons in the post-lesional brain in vivo .…”
Section: Resultsmentioning
confidence: 78%
“…Interestingly, it had previously been shown that the ionotropic NMDA glutamate receptor subunit NR1 is found on the growth cone of DA neurons and suggested that axonal outgrowth in primary DA neurons can be driven by an autocrine glutamate-mediated feedback loop (Schmitz et al, 2009). In addition, we have also shown that post-natal dorsal striatal cells repress Vglut2 expression in cultured DA neurons (Fortin et al, 2019).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations